The gamification of learning and instruction fieldbook : ideas into practice - Kapp, Karl M., ....-; Blair, Lucas, ....-; Mesch, Rich, ....- (San Francisco : Wiley, 2014)
Following Karl Kapp's earlier book The Gamification of Learning and Instruction, this Fieldbook provides a step-by-step approach to implementing the concepts from the Gamification book with examples, tips, tricks, and worksheets to help a learning professional or faculty member put the ideas into practice. The Online Workbook, designed largely for students using the original book as a textbook, includes quizzes, worksheets and fill-in-the-blank areas that will help a student to better understand the ideas, concepts and elements of incorporating gamification into learning.